Friday

August 29, 2014

August 29, 2014

Posted by **Stacey** on Sunday, May 6, 2007 at 1:53pm.

(cosx)(tanx + sinx cotx)=sinx+cos(squared)x

i need steps to show how i got the answer

generally, it is a good idea to change all trig ratios to sines and cosines, and start with the more complicated-looking side.

so....

LS =

cosx(sinx/cosx + sinx(cosx/sinx)

=

=

just expand and simplify and the RS pops out

**Related Questions**

Trigonometry. - ( tanx/1-cotx )+ (cotx/1-tanx)= (1+secxcscx) Good one! ...

Pre-Calc - Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= ...

trigonometry - can i use factoring to simplify this trig identity? the problem ...

drwls - My previous question: Verify that (secx/sinx)*(cotx/cscx)=cscx is an ...

Math - Im really struggling with these proving identities problems can somebody ...

maths - trigonometry - I've asked about this same question before, and someone ...

Trig........ - I need to prove that the following is true. Thanks (cosx / 1-sinx...

trig - express this in sinx (1/ cscx + cotx )+ (1/cscx- cotx) i got 2sinx is ...

Trigonometry Check - Simplify #3: [cosx-sin(90-x)sinx]/[cosx-cos(180-x)tanx] = [...

Mathematics - Trigonometric Identities - Prove: sinx + tanx = tanx (1 + cosx) ...